Generation of geometric irregularities as random disturbances causing rail cab oscillations - A. N. Savoskin; N. S. Lavlinskaya (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Solving the dynamics problems of rail cabs requires specifying the kinematic disturbance of their oscillations represented through equivalent vertical and horizontal geometric irregularities of the left and right rails. The formation of such four-dimensional disturbance involves the generation of multivariate random processes based on auto- and cross-correlation functions or spectral and cross-spectral densities of actual recordings of rail track irregularities. The paper refines the probabilistic properties of the disturbances that cause rail cab oscillations and develops a new simplified method for their generation.Materials and methods. The paper provides a probabilistic analysis of long-term (over 14 km) recorded natural rail track irregularities and an approximation of the obtained probabilistic properties with analytical expressions corresponding to differentiable random processes. The parameters of these processes were found by the least-square method. The new method generated random irregularities for the track coordinate using a multivariate shaping filter whose impulse characteristics were found with analytical expressions of auto- and cross-correlation functions.Results. The authors refined the probabilistic values of rail track irregularities that may be used to specify disturbances of rail cab oscillations when solving dynamics problems and proposed a simplified irregularity generation method for the track coordinate argument that provides high convergence to the previously obtained data.Discussion and conclusion. The received probabilistic characteristics may be applied to generate a multivariate random irregularities when examining the oscillations of different type rail cabs occurring at different speeds movement. The proposed simplified generation method reduces the time for simulating disturbances.